Analyses of pig genomes provide insight into porcine demography and evolution - Groenen, Martien A. M.; Archibald, Alan L.; Uenishi, Hirohide; Tuggle, Christopher K.; Takeuchi, Yasuhiro; Rothschild, Max F.; Rogel-Gaillard, Claire; Blecha, Frank; Sang, Yongming (My University, 2012)
For 10,000 years pigs and humans have shared a close and complex relationship. From domestication to modern breeding practices, humans have shaped the genomes of domestic pigs. Here we present the assembly and analysis of the genome sequence of a female domestic Duroc pig (Sus scrofa) and a comparison with the genomes of wild and domestic pigs from Europe and Asia. Wild pigs emerged in South East Asia and subsequently spread across Eurasia. Our results reveal a deep phylogenetic split between European and Asian wild boars ~1 million years ago, and a selective sweep analysis indicates selection on genes involved in RNA processing and regulation. Genes associated with immune response and olfaction exhibit fast evolution. Pigs have the largest repertoire of functional olfactory receptor genes, reflecting the importance of smell in this scavenging animal. The pig genome sequence provides an important resource for further improvements of this important livestock species, and our identification of many putative disease-causing variants extends the potential of the pig as a biomedical model.
Keywords: Pig genomes; Duroc pig; Sus scrofa; Porcine demography; Porcine evolution